Financial Management, Marketing Management, Leadership Competencies, and Entrepreneurial Success: Conceptual and Empirical Review - OYEKU , Oyedele Matthew; ADEJUWON , Joshua Adewale; OYEKU, Bonuola Victoria (Covenant Journal of Entrepreneurship, 2024)
The goal of setting up an enterprise by the entrepreneur is to make a profit. With the current global inflation, many small and medium enterprises find it difficult to survive in a business environment characterized by hostility and uncertainties. To succeed, therefore, entrepreneurs need a broad base of competencies that they need to develop and harness to influence enterprise success properly. The concept of entrepreneurial competency is fairly deep because it involves the personal characteristics of an entrepreneur and how the entrepreneur reacts when confronted with various tasks and situations related to the venture’s operations. This paper identified financial, marketing, and leadership competencies as key dimensions of entrepreneurial competency necessary to start and run a business successfully. A thorough conceptual review of the three dimensions has been carried out to provide a deep understanding. Also, an empirical review was carried out on the three dimensions to understand their effects on or relationships with four dimensions of success: profitability, sales growth, customer satisfaction, and competitiveness. It is recommended that researchers devote more attention to studying these three dimensions of entrepreneurial competency as entrepreneurial success determinants to address the alarming rate at which small and medium enterprises are closing down. The government should provide the necessary financial support to researchers in this area.